A sensitive bioassay to measure NOD1/2 ligands in human serum reveals differential postprandial NOD2 activation - Biber, Lucy; Schart, Nadine; Bosy-Westphal, Anja; Kufer, Thomas A. (Frontiers in Nutrition, 2025)
Food intake is associated with the occurrence of components and metabolites from the gut microbiota in the bloodstream. Using a widely utilised cell-based assay to measure bacterial peptidoglycan via pattern-recognition receptor activation, we found that the performance of this assay is significantly influenced by the presence of other serum components. To address this challenge, an alternative luciferase-based reporter assay protocol was established to accurately measure NOD1 and NOD2 activation by serum samples with high sensitivity. Utilising postprandial human serum samples, we tested this assay and showed that the concentration of NOD2-activating ligands differed in the postprandial phase. Together, we provide a protocol to measure NOD1/2 activation by human serum samples and highlight a role for NOD2 in the postprandial response.